"We commited ten of our number to the silent tomb": The archaeological evidence of the Walnut Creek massacre, Kansas (14BT301). (3rd April 2021) - Scott, Douglas D.
Abstract : Heavy rains and subsequent bank erosion in 1973 exposed the skeletal remains of 10 men and boys on Walnut Creek in Barton County, Kansas. The site (14BT301) has not been fully reported, and this effort is a step in that direction. The human remains were determined to include two men of African ancestry, and eight of white Euro-American ancestry. Historical research determined the burials are associated with the so-called Walnut Creek massacre where 10 teamsters were killed by Kiowa and Arapaho on 18 July 1864. Artifacts related to clothing they were wearing when interred are analyzed and reported. Thirteen iron projectile points that likely contributed to the deaths of the 10 are also analyzed and reported. The analytical results are compared to a rich historic documentary record which illustrates that travel on the Santa Fe Trail was not always benign.